Ka-Band High-Gain Omnidirectional Dual-Reflector Antenna - Silva, Lucas R. G. [UNESP]; Simionato, Eligia [UNESP]; Aldaya, Ivan [UNESP]; Oliveira, Jose A. [UNESP]; Zang, Sandro R.; De Medeiros, Everton C.; Ribeiro, Raul O. [UNESP]; Da Rosa, Guilherme S. [UNESP]; Penchel, Rafael A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This work presents performance analysis of a high-gain omnidirectional dual-reflector antenna designed for operation in the Ka-band (26-40 GHz). A TEM-mode coaxial horn feeds the reflector system to ensure vertical polarization and wide operating bandwidth. A prototype was fabricated using CNC (for the reflector parts) and additive manufacturing techniques with metal and polymer plastics (for the horn feed and radome parts). The fabricated coaxial horn exhibits an impedance bandwidth (with reflection coefficient less than -10 dB) covering the entire Ka-band, and a peak realized gain of about 11.5 dBi. The complete antenna system, using aluminum reflectors and a PLA cylindrical radome, demonstrates an simulated impedance bandwidth covering the entire Ka-band and a maximum directivity of about 12.5 dBi.
Keywords: additive manufacturing; coaxial horn; dual-reflector antenna; horn antenna; Ka-band; mil-limeter wave; Omnidirectional antenna